Adsorption of bovine alpha-lactalbumin on suspended solid nanospheres and its subsequent displacement studied by NMR spectroscopy - Engel, Maarten F M (Langmuir : the ACS journal of surfaces and colloids, 2004)
Detailed knowledge of the adsorption-induced conformational changes of proteins is essential to understand the process of protein adsorption. However, not much information about these conformational changes is available. Here, the adsorption of calcium-depleted (APO)- and calcium-containing (HOLO)-bovine alpha-lactalbumin (BLA) on suspended solid polystyrene nanospheres and their subsequent displacement by a surfactant are studied by NMR spectroscopy. To our knowledge, this is the first time that adsorption of proteins on solid nanospheres, with both components present in the NMR sample, is studied by this method. High-quality one-dimensional and two-dimensional 1H NMR spectra of nonadsorbed APO- and HOLO-BLA in the presence of BLA- and/or surfactant-covered solid polystyrene nanospheres in suspension are obtained using standard NMR procedures. BLA and surfactant molecules that are adsorbed on the polystyrene nanospheres give rise to extremely broadened proton resonances. This can be exploited to determine the amount of adsorbed protein and of adsorbed surfactant in a system containing protein, nanospheres, and surfactant, without disturbing the equilibrium of the system. Two-dimensional 1H NMR spectroscopy shows that the chemical shifts of the backbone amide protons of HOLO-BLA after its adsorption and subsequent displacement from polystyrene nanospheres by the surfactant 3-[(3-cholamidopropyl)-dimethylammonio]-1-propanesulfonate (CHAPS) are identical to those of native HOLO-BLA. The adsorption-induced unfolding of BLA to a molten globule state on polystyrene nanospheres is thus fully reversible at the residue level upon CHAPS-induced displacement of BLA. The latter is the now fulfilled essential requirement that enables the future indirect study, at the residue level, of the conformational characteristics of BLA adsorbed on polystyrene nanospheres by hydrogen/deuterium exchange and NMR spectroscopy. The results presented show that NMR spectroscopy is clearly feasible to study the adsorption of BLA on suspended polystyrene nanospheres. This technique should be applicable to the study of the adsorption of other proteins on other surfaces as well